PENGARUH LITERASI KEUANGAN, LOCUS OF CONTROL, DAN GAYA HIDUP TERHADAP PENGELOLAAN KEUANGAN PRIBADI PADA GENERASI Z DI KABUPATEN BANYUMAS - Ramadhani, Kartika; Putri, Puspita Lianti; Sari, Kartika Dwi Chandra (Fakultas Ekonomi dan Bisnis, 2023)
Managing finances in the industrial era 4.0 is an important activity that must be carried out by individuals. Achieving prosperity is highly dependent on the ability to manage finances. The purpose of this study was to determine the effect of financial literacy, locus of control, and lifestyle on personal financial management in generation Z in Banyumas Regency. The data source is primary data by distributing google form questionnaires. The research method uses an explanatory type quantitative approach. The sampling technique used was purposive sampling and obtained 165 generation Z in Banyumas Regency with data analysis using multiple linear regression analysis. The results of partial and simultaneous statistical testing show a positive effect of financial literacy, locus of control, and lifestyle on personal financial managementKeywords: Financial Literacy, Locus of Control, Lifestyle, Personal Financial Management, Generation Z